Ischemia-Reperfusion Injury of Sciatic Nerve in Rats and Protective Role of Benidipine Hydrochloride - Çakir, Tayfun; Yücetaş, Şeyho Cem; Yazici, Gülce Naz; Sunar, Mukadder; Arslan, Yusuf Kemal; Kayaci, Selim; Süleyman, Halis (European Journal of Therapeutics, 2021)
Objective: Benidipine is an antihypertansive agent which elicits vasodilatation of arteries by blocking Ca2þ. The aim of this study is to investigate the neuroprotective effects of benidipine on rat sciatic nerves exposed to ischemia and reperfusion (I/R). Method: 30 male Wistar Albino rats were used in this study. The rats were divided into three groups(n=10 per group). I/R procedure was administered to the IR group, 10 lg/kg/day, i.v. benidipine was given for 2 hours (h) to the BIR group before I/R procedure. And a sham group (SG) was created. Next, histopathological and biochemical investigations were performed on sciatic nerve tissues. Superoxide dismutase (SOD), Malondialdehyde (MDA) and glutathione (GSH) were analyzed as oxidative stress markers; interleukin 1 beta (IL-1b) and tumor necrosis factor alpha (TNF-a) were analyzed as inflammatory stress markers in biochemical tests. Results: Axonal swelling, myelin loss and disorganisation were seen in the IR group. Schwann cells showed hypertrophy, hyperplasia, blood vessels were seen as congested. But these results were under normal values and almost similiar between BIR and SG groups. In the BIR group ischemic fibere degeneration score was significiantly lower than IR group. And MDA, TNF-a, IL-1b values higher, GSH and SOD values were lower in the IR group, but in the BIR group all these values were kept within normal limits. Conclusion: This study showed that benidipine reduced oxidative stress and inflammation in rat sciatic nerve after I/R injury